Prevalence of depression and its association with health-related quality of life in people with heart failure in low- and middle-income countries: A systematic review and meta-analysis. - Henok Mulugeta; Peter M Sinclair; Amanda Wilson (PLoS ONE, 2023)
Introduction Heart failure is a growing public health concern around the world. People with heart failure have a high symptom burden, such as depression, which affects health-related quality of life (HRQoL). The objective of this systematic review and meta-analysis was to estimate the pooled prevalence of depression and evaluate its association with HRQoL among people with heart failure in low- and middle-income countries (LMICs). Methods This systematic review was conducted in accordance with the JBI methodology. Electronic databases such as MEDLINE, PsycINFO, EMBASE, CINAHL, Web of Science, Scopus and JBI EBP were searched to identify relevant studies published from January 2012 to August 2022. The methodological quality of each article was assessed using relevant JBI critical appraisal instruments. A random-effects model was employed to estimate the pooled prevalence of depression. Heterogeneity across the studies was investigated using Cochrane's Q test and I2 statistic. The Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines 2020 were followed for reporting the results. All statistical analyses were performed using STATA version 17 software. Results After screening, a total of 21 eligible articles with 5074 participants with heart failure were included in this review. The pooled prevalence of depression among people with heart failure in LMICs was 51.5% (95% CI = 39.7, 63.3%, I2 = 99.00%). Subgroup analysis revealed, the highest prevalence in studies whose participants were in-patients, and from the Middle East and North Africa, and studies utilizing Becks Depression Inventory (BDI). Depression was positively associated with HRQoL. Conclusion This review revealed that almost half of all people with heart failure in low- and middle-income countries have comorbid depression. People with heart failure and depressive symptoms had poor HRQoL. Therefore, early screening of depression is critical for improving HRQoL in this population. Systematic review registration: PROSPERO CRD42022361759.